THE INTENSITY OF E-COMMERCE USAGE AND THE CONSUMPTIVE LIFESTYLE OF PSIK 24 STUDENTS FROM AN ISLAMIC EDUCATION PERSPECTIVE - Alfarizi Wijaya; Nafil Rizq Trianto; Calvin Sahputra Buulolo; Irfan Zaky Muchtar (IAIN Bone, 2026)
The rapid growth of e-commerce has significantly altered university students' consumption patterns, often facilitating a consumptive lifestyle. This study aims to examine the causal effect of e-commerce usage intensity on the consumptive lifestyle of PSIK 24 students at Universitas Negeri Medan, analyzed through the perspective of Islamic Education. Employing a quantitative approach with a survey method, data were collected via structured questionnaires from a saturated sample of 30 students. The data were analyzed using descriptive statistics and simple linear regression to test the causal relationship. The findings reveal a significant positive effect of e-commerce usage intensity on consumptive lifestyle (p<0.05), accounting for 41% of the variance in students' consumptive behavior. Descriptively, students exhibited high e-commerce engagement and notable consumptive tendencies driven by digital promotions. From an Islamic Education perspective, such behavior reflects israf (excessiveness), which contradicts the principles of wasathiyah (moderation) and qana’ah (contentment). Consequently, students must internalize Islamic values and strengthen self-control to manage their consumption behavior in the digital era responsibly